Interaction Between CD34+ Fibrocytes and Airway Smooth Muscle Promotes IL-8 Production and Akt/PRAS40/mTOR Signaling in Asthma - Lin, Ting-Yu; Chang, Po-Jui; Lo, Chun-Yu; Lo, Yu-Lun; Yu, Chih-Teng; Lin, Shu-Min; Kuo, Chih-His Scott; Lin, Horng-Chyuan (Frontiers in Medicine, 2022)
Background: The circulating progenitor cells of fibroblasts (fibrocytes) have been shown to infiltrate the airway smooth muscle compartment of asthma patients; however, the pathological significance of this discovery has yet to be elucidated. This study established a co-culture model of airway smooth muscle cells (ASMCs) and fibrocytes from asthmatic or normal subjects to evaluate innate cytokine production, corticosteroid responses, and signaling in ASMCs. Methods: CD34+ fibrocytes were purified from peripheral blood of asthmatic (Global Initiative for Asthma treatment step 4 to 5) and normal subjects and cultured for 5 7 days. In a transwell plate, ASMCs were co-cultured with fibrocytes at a ratio of 2:1, ASMCs were cultured alone (control condition), and fibrocytes were cultured alone for 48 hours. Measurements were obtained of interleukin-8 (IL-8), IL-6, IL-17, thymic stromal lymphopoietin, and IL-33 levels in the supernatant and IL-33 levels in the cell lysate of the co-culture. Screening for intracellular signaling in the ASMCs after stimulation was performed using condition medium from the patients’ co-culture (PtCM) or IL-8. mRNA and western blot analysis were used to analyze AKT/mTOR signaling in ASMCs stimulated via treatment with PtCM or IL-8. Results: Compared with ASMCs cultured alone, IL-8 levels in the supernatant and IL-33 levels in the ASMCs lysate were significantly higher in samples co-cultured from asthmatics, but not in those co-cultured from normal subjects. Corticosteroid-induced suppression of IL-8 production was less pronounced in ASMCs co-cultured with fibrocytes from asthma patients than in ASMCs co-cultured from normal subjects. ASMCs stimulated using PtCM and IL-8 presented elevated AKT substrate PRAS40 levels. Treatment with IL-8 and PtCM increased mRNA expression of mTOR and P70S6 kinases in ASMCs. Treatment with IL-8 and PtCM also significantly increased phosphorylation of AKT and mTOR subtract S6 ribosomal protein in ASMCs. Conclusion: The interaction between ASMCs and fibrocytes from asthmatic patients was shown to increase IL-8 and IL-33 production and promote AKT/mTOR signaling in ASMCs. IL-8 production in the co-culture from asthmatic patients was less affected by corticosteroid than was that in the co-culture from normal subjects. Our results elucidate the novel role of fibrocytes and ASMCs in the pathogenesis of asthma.